Comparison of prevalence and associated factors of depressive disorder between patients with head and neck cancer and those with lung cancer at a tertiary hospital in Taiwan: a cross-sectional study. Issue 6 (29th June 2020) - Lee, Yu; Hung, Chi-Fa; Chien, Chih-Yen; Lin, Pao-Yen; Lin, Meng-Chih; Wang, Chin-Chou; Lu, Hung-I; Chen, Yung-Che; Chong, Mian-Yoon; Wang, Liang-Jen
Abstract : Objective: Depression is a common comorbidity in cancer patients. This study aimed to compare the prevalence and associated factors of depressive disorder between patients with head and neck cancer (HNC) and those with lung cancer (LC). Design: This study used a cross-sectional design with consecutive sampling. Setting: A medical centre (Kaohsiung Chang Gung Memorial Hospital, Taiwan). Participants: Patients for the study were recruited from the HNC and LC outpatient clinic and inpatient ward from March 2016 to February 2018. Patients with HNC and LC were enrolled and assessed using the Mini International Neuropsychiatric Interview (MINI). Primary and secondary outcome measures: The primary outcome was psychiatric diagnoses assessed using the MINI. The secondary outcomes were psychological well-being assessed using the Beck Anxiety Inventory, Taiwanese Depression Questionnaire, Brief Fatigue Inventory, Numeric Pain Rating Scale and the List of Threatening Experiences Questionnaire. Results: In total, 113 HNC patients and 104 LC patients were recruited for the study. The most common psychiatric comorbidity of HNC patients was alcohol use disorder (49.6%), followed by adjustment disorder (20.4%) and depressive disorder (11.5%). The most common psychiatric comorbidity of LC patients was depressive disorder (25.0%), followed by adjustment disorder (17.3%), alcohol use disorder (3.8%) and insomnia disorder (3.8%). Among HNC patients, a self-harm history was positively associated with depression (OR=11.91; 95% CI, 1.47 to 96.83), and a higher educational level was negatively associated with depression (OR=0.77; 95% CI, 0.66 to 0.91). Among LC patients, severity of stressor (OR=2.78; 95% CI, 1.50 to 5.15) and severity of anxiety (OR=1.18; 95% CI, 1.04 to 1.34) were two significant factors associated with depression. Conclusion: We reported the prevalence and associated factors of depression between patients with HNC and those with LC. Clinicians should be aware of this comorbidity and the associated risk factors, and conduct intervention programmes to prevent these cancer patients from developing depression.